1996
DOI: 10.1016/s0550-3213(96)00486-5
|View full text |Cite
|
Sign up to set email alerts
|

Nucleon parton distributions at low normalization point in the large Nc limit

Abstract: At large N c the nucleon can be viewed as a soliton of the effective chiral lagrangian. This picture of nucleons allows a consistent nonperturbative calculation of the leadingtwist parton distributions at a low normalization point. We derive general formulae for the polarized and unpolarized distributions (singlet and non-singlet) in the chiral quark-soliton model. The consistency of our approach is demonstrated by checking the baryon number, isospin and total momentum sum rules, as well as the Bjorken sum rul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
387
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 233 publications
(413 citation statements)
references
References 31 publications
25
387
1
Order By: Relevance
“…the unexpectedly small quark spin fraction of the nucleon, can be explained at least qualitatively with no need of a large gluon polarization at the low renormalization scale [5], [19]. Finally, the model predicts a sizably large isospin asymmetry also for the spin-dependent sea-quark distributions, which we expect will be confirmed by near future experiments [10], [13], [18], [20].…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…the unexpectedly small quark spin fraction of the nucleon, can be explained at least qualitatively with no need of a large gluon polarization at the low renormalization scale [5], [19]. Finally, the model predicts a sizably large isospin asymmetry also for the spin-dependent sea-quark distributions, which we expect will be confirmed by near future experiments [10], [13], [18], [20].…”
Section: Introductionsupporting
confidence: 74%
“…Among others, most important in the above-explained context is its field theoretical nature, i.e. the proper account of the polarization of Dirac sea quarks, which enables us to make reasonable estimation not only of quark distributions but also of antiquark distributions [10]- [13]. It has already been shown that, without introducing any adjustable parameter, except for the initial-energy scale of the Q 2 -evolution, the CQSM can describe nearly all the qualitatively noticeable features of the recent high-energy deep-inelastic scattering observables.…”
Section: Introductionmentioning
confidence: 99%
“…The χQSM has been derived from the instanton model of the QCD vacuum [16]. Due to the field-theoretical nature of the χQSM, the quark and antiquark distribution functions computed in the model satisfy all general QCD requirements (positivity, sum rules, inequalities) [17]. The model results for the known distribution functions -f q 1 (x), fq 1 (x) and g q 1 (x) -agree within (10 -30)% with phenomenological parameterizations [18].…”
Section: Ingredients For Prediction: H ⊥ 1 and H A 1 (X)mentioning
confidence: 99%
“…These inequalities hold for each quark flavor f . In the leading order of the large N c limit we have for the u and d distribution functions of the proton [10,11]:Therefore the set of usual inequalities (1) takes the following form in the large N c limit(large N c old bounds) (3) Note that in the last inequality (3) we have the absolute value of ∆ L q u in contrast to Soffer inequality at finite N c (1). Actually we combined two Soffer inequalities for f = u, d (1) and we made use of the large N c relation ∆ L q u = −∆ L q d (see eq.…”
mentioning
confidence: 99%
“…These inequalities hold for each quark flavor f . In the leading order of the large N c limit we have for the u and d distribution functions of the proton [10,11]:…”
mentioning
confidence: 99%